New representatives of deep water echiurids (Alomasoma belyaevi Zenk. sp. n. and Choanostoma filatovae sp. n.) in the Pacific - Zenkevitch L. A. (Zoologicheskii Zhurnal, 1964)
A new species Alomasoma belyaevi which is close to A. nordpacifica Zenk., but is drastically distinguished by the presence of very many long appendices on anal glands. (fig. 1: A — the appearance of the worm from the ventral side, B — nephridia and anal glands on a worm dissected from the dorsal side) is described by the author from the collections of the «Vityaz». The worm was found at the station 4173 at a depth of 2,826–2,843 m (44°53' N. L. and 128°32.1' W. L.). A description is also given of a new species Choanostoma filatovae (fig. 2, A–D) of the genus previously described by L. A. Zenkevich for the Arabian Sea of the Indian Ocean (Choanostoma bruuni Zenk.). Ch. filatovae was found at the station 3223 at a depth of 1,693 m (39°45' N. L. and 143°22' E. L.), its fragments being found at the station 3120 (20°24' N. L. and 122°30' E. L.) at a depth of 3,111 m. After the publication of my paper containing the description of a new genus Choanostoma (1964) I have been kindly informed by Dr. A. V. Yankovsky that this genus name had been attached by Wang in 1930 to the newly described infusoria Choanostoma pingi. However Echiuroidea and Infusoria are very different groups in the system of the animals and I will not change the old genus name Choanostoma.
In Russian with English summary